Antioxidant and Antimicrobial Activities of Some New Synthesized Triazole, Thiazolone, and Thiazine Containing Fused Rings of Imidazopyridine - Hamd, Amera H.; Al-Lami, Naeemah (Iraqi Journal of Science, 2024)
Several heterocyclic compounds bearing an imidazo(1,2a)pyridine moiety have been synthesized in this work, including triazole, thiazol, and thiazolone. This was done by condensation of 2-aminopyridine with 2-aminopyridine with 4-bromophencyl bromide or 4-phenylphencyl bromide to produce 2-substituted phenyl imidazo(1,2a)pyridine compounds 1 and 2. The Vilsmeier-Haak reaction was used to create the aldehyde group at position 3 of the 2-substituted phenyl imidazo(1,2a)pyridine ring (3 and 4). The reaction of compounds 3 and 4 with thiosemicarbazide afforded thiosemicarbazone derivatives 5 and 6 in 66 and 70% yields, respectively. These derivatives (5 and 6) were then subjected to three different cyclization reactions to obtain 1,3-thiazolone (7 and 8), 1,2,4-triazole (9 and 10), and 1,3-thiazole (11 and 12) derivatives. The FT-IR spectroscopy was used to confirm the structure of these derivatives, and the 1H NMR spectroscopy was used for some of them. A few of the produced compounds were examined for antimicrobial and antioxidant activities